THEORETICAL ANALYSIS AND EXPERIMENTAL STUDY USED FOR SOUND QUALITY OF INVERTER AIR CONDITIONER NOISE - XUE WeiFei; CHEN Jun; CHEN Jin; XU Hao; ZHANG Hao (Jixie qiangdu)
The A-weight sound level is difficult to evaluate the annoyed noise of the inverter air conditioner,so it is necessary to establish the sound quality and give objective evaluate parameters,such as loudness,sharpness,roughness,psychoacoustic annoyance etc. The sound quality software is developed to analyze outdoor noise of MIDEA inverter air conditioner and the competitive product; the main difference is low-frequency noise. Then,the"rock"noise and periodic"buzz"noise are analyzed in detail,and system dynamic balance and beat are main reasons. Some methods are obtained to eliminate the lowfrequency noise and can improve the sound quality. These methods can potentially become a powerful air conditioner sound evaluation tool in inverter air conditioner field.